Internal enhancement of DNA damage by a novel bispecific antibody‐drug conjugate‐like therapeutics via blockage of mTOR and PD‐L1 signal pathways in pancreatic cancer. (25th January 2019) - Cao, Rui; Song, Wenping; Ye, Cheng; Liu, Xiujun; Li, Liang; Li, Yi; Yao, Hongjuan; Zhou, Xiaofei; Li, Liang; Shao, Rongguang
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a refractory malignant tumor with poor prognosis, limited chemotherapeutic efficacy, and only about 5% of 5‐year survival rate. We generated a dual‐targeting ligand‐based lidamycin (DTLL) to investigate its efficacy against pancreatic cancer after preparing its precursor, DTLP. DTLP was shown specifically binding to EGFR and HER2 on cell surface, followed by endocytosis into cytoplasm of pancreatic cancer cells. DTLL significantly promoted apoptosis and cell cycle arrest at G2/M stages and inhibited cell proliferation. Pancreatic tumors of either MIA‐paca‐2 cell line‐derived (CDX) or patient‐derived xenograft (PDX) mouse models were significantly regressed in response to DTLL. It suggested that DTLL might be a highly potent bispecific antibody‐drug conjugate (ADC)‐like agent for pancreatic cancer therapy. LDM is known to function as an antitumor cytotoxic agent by its induction of DNA damage in cancer cells, therefore, DTLL, as its derivative, also showed similar cytotoxicity. However, we found that DTLL might reverse the AKT/mTOR feedback activation induced by LDM at the first time. The results from both in vitro and in vivo experiments suggested that DTLL enhanced DNA damage via EGFR/HER2‐dependent blockage of PI3K/AKT/mTOR and PD‐L1 signaling pathways in cancer cells, leading to the inhibition of cell proliferation and immunosurveillance escape from pancreatic tumor. Our studies on DTLL functional characterization revealed its novel mechanisms on internal enhancement of DNA damage and implied that DTLL might provide a promising targeted therapeutic strategy for pancreatic cancer. Abstract : DTLP showed bispecific binding activities to EGFR/HER‐2 in vitro and in vivo. DTLL showed potent anti‐pancreatic cancer efficacy in CDX and PDX mouse models of human pancreatic cancer 3. DTLL had an antineoplastic effect by inhibited AKT/mTOR and PD‐1/PD‐L1 signal pathways in human pancreatic cancer.